Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1021/acsomega.0c00620
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Long-Persistent Phosphorescence by Solid-State Reaction and Mixing of Spectrally Different Phosphors

Abstract: Rare-earth-doped oxide-based phosphors have attracted great interest as light-emitting materials for technical applications and fundamental research because of their high brightness, tunable emission wavelength, and low toxicity, as well as chemical and thermal stability. The recent development of rare-earth-doped nanostructured materials showed improved phosphorescence characteristics, including afterglow and lifetime. However, the development of highly efficient phosphors remains challenging in terms of brig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Applying this phenomenon, Zhang et al demonstrated the ratiometric temperature sensing of LaOBr:Ce 3+ ,Tb 3+ over a wide temperature-sensing range (293–443 K) with a sensitivity of 0.42% K −1 [ 103 ]. This approach has also been recently demonstrated in lanthanide-codoped aluminate phosphors with various colors, such as SrAl 2 O 4 :Eu 2+ ,Dy 3+ , Sr 4 Al 14 O 25 :Eu 2+ ,Dy 3+ , and CaAl 2 O 4 :Eu 2+ ,Nd 3+ as green, blue, and violet phosphors, respectively [ 14 ]. Novel protocols have been developed based on the effect of energy transfer between spectrally different phosphors, and they were noted to significantly improve the afterglow intensities and lifetimes of green and blue phosphors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Applying this phenomenon, Zhang et al demonstrated the ratiometric temperature sensing of LaOBr:Ce 3+ ,Tb 3+ over a wide temperature-sensing range (293–443 K) with a sensitivity of 0.42% K −1 [ 103 ]. This approach has also been recently demonstrated in lanthanide-codoped aluminate phosphors with various colors, such as SrAl 2 O 4 :Eu 2+ ,Dy 3+ , Sr 4 Al 14 O 25 :Eu 2+ ,Dy 3+ , and CaAl 2 O 4 :Eu 2+ ,Nd 3+ as green, blue, and violet phosphors, respectively [ 14 ]. Novel protocols have been developed based on the effect of energy transfer between spectrally different phosphors, and they were noted to significantly improve the afterglow intensities and lifetimes of green and blue phosphors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Eu 2+ dopant ions in SrAl 2 O 4 and Sr 4 Al 14 O 25 are known to generate different emission wavelengths owing to their different crystalline structures (orthorhombic for Sr 4 Al 14 O 25 and monoclinic for SrAl 2 O 4 ) [ 44 , 58 , 59 ]. Kim et al synthesized SrAl 2 O 4 :Eu 2+ ,Dy 3+ and Sr 4 Al 14 O 25 :Eu 2+ ,Dy 3+ as green and blue phosphors, respectively, by taking advantage of the different emission wavelengths [ 14 ].…”
Section: Strontium Aluminate Phosphorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past decade, inorganic luminescent materials have enabled significant developments in optoelectronic devices, including solid-state lasers, lighting, and displays. 14 Recently, host materials with the doping of lanthanide (Ln) ions and/or transition metal (TM) ions in the lattice to function as luminescent centers have gained specific attention. 15 The unique ladder-like arranged energy levels of Ln and TM ions enable the generation of photons efficiently in a set of a spectral region ranging from ultraviolet (UV) to visible and near-infrared (NIR).…”
Section: Introductionmentioning
confidence: 99%